Induction of Fetal Hemoglobin In Vivo Mediated by a Synthetic γ-Globin Zinc Finger Activator - Flávia C. Costa; Halyna Fedosyuk; Renee Neades; Johana Bravo de Los Rios; Carlos F. Barbas; Kenneth R. Peterson (Anemia)
Sickle cell disease (SCD) and β-thalassemia patients are phenotypically normal if they carry compensatory hereditary persistence of fetal hemoglobin (HPFH) mutations that result in increased levels of fetal hemoglobin (HbF, γ-globin chains) in adulthood. Thus, research has focused on manipulating the reactivation of γ-globin gene expression during adult definitive erythropoiesis as the most promising therapy to treat these hemoglobinopathies. Artificial transcription factors (ATFs) are synthetic proteins designed to bind at a specific DNA sequence and modulate gene expression. The artificial zinc finger gg1-VP64 was designed to target the −117 region of the Aγ-globin gene proximal promoter and activate expression of this gene. Previous studies demonstrated that HbF levels were increased in murine chemical inducer of dimerization (CID)-dependent bone marrow cells carrying a human β-globin locus yeast artificial chromosome (β-YAC) transgene and in CD34+ erythroid progenitor cells from normal donors and β-thalassemia patients. Herein, we report that gg1-VP64 increased γ-globin gene expression in vivo, in peripheral blood samples from gg1-VP64 β-YAC double-transgenic (bigenic) mice. Our results demonstrate that ATFs function in an animal model to increase gene expression. Thus, this class of reagent may be an effective gene therapy for treatment of some inherited diseases.